Perfil epidemiológico de pacientes com candidúria internados em hospitais privados e público de Cuiabá – MT - Santana, Milena Melges Pesenti de (2016)
Candida yeasts are considered the main agents of nosocomial fungal infections. The distribution of species varies with the characteristics of each region and the demographic group of individuals studied. Thus, this study aimed to establish the epidemiological profile of candiduria in patients hospitalized in Cuiabá (MT), from march to august 2015. Three private hospitals and public hospitals participated in the study. A total of 93 patients were evaluated candiduria, occurring more frequently for the species C. tropicalis (37.6%; n=35), followed by C. albicans (36.6%; n=34), C. glabrata (19.3%; n=18), psilosis complex (4.3%; n=4), C. lusitaniae (1.1%; n=1), C. krusei (1.1%; n=1). Antibiotic therapy (100%) and the use of indwelling urinary catheter (89.2%) were the most frequent exposure factors. Antifungal treatment was initiated in 65.6% of patients. The initiation of therapy was 26% higher in patients who had urine cultures with growth ≥ 105 CFU/mL (OR=1.26; p=0.035), anidulafungin being the most used antifungal. The death was 48% higher among patients with candiduria who had renal failure and 51% lower among those not treated with micafungin. Candidemia concomitant to candiduria occurred in 8.6% (n=8) of the cases. Considering the species recovered in the blood and urine, only one patient had genetically distinct clinical isolates.